Knowledge production, interdisciplinarity, and structuralism - DOI: 10.3395/reciis.v3i3.271en - Maria de Fátima Gonçalves Moreira Tálamo (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This paper presents the organization of modern science, identifying knowledge production occurrences according to formal and informal contexts, and its paradigmatic transition to post-modernity, resorting to interdisciplinarity, the workings of which, following the principle of the economy of symbolic systems, allow repetition with different meaning and the consolidation of humanities. This phenomenon is exemplified by structuralism which, in contemporary times, continues to play an important role in the organization of new fields of investigation, such as the imprecise sciences and information science.